Reconhecimento e reflexividade da alteridade gay na sala de aula - Silva, Darkson Kleber Alves da (2017)
This research analyzes the phenomenon of recognition and reflexivity of the teacher vis-à-vis gay alterity in the classroom. The processes of communication by type of contact and modes of interaction between gay teacher and gay students in the school context are analyzed. The theoretical-methodological basis of the research is based on the constructivist perspective of social analysis, on autobiographical approaches and interpretive ethnography. Qualitative research is applied. Oral Life Report (personal and professional), field journal and semi-structured interview were the instruments of data collection. The results of the research indicate the existence of visibility, recognition and reflexivity of gay alterity in school pedagogical contexts by gay teachers as a result of the intentional symbolic communication process among those involved in the classroom. Three types of contact between gay alterities in the classroom were found: (a) avoidant peripheral contact; (b) marginal exclusionary contact and (c) inclusive dialogic contact. These elements allow us to affirm that the recognition and reflexivity of gay alterity in the classroom is explained by two different types of communication: (1) Interreflex Symbolic Communication and (2) Symbolic Exorreflex Communication. Finally, the phenomena of recognition and reflexivity of the gay teacher are inseparable from the personal and collective emancipation of the social actors still invisible in the school system with respect to diversity, social significance, silencing, oppression and (in) visibility of gay alterity in the classroom of class.